Responsiveness Pelayanan E-Ktp Di Kecamatan Ujungberung Kota Bandung - Leni Oktopiani; Izjtihad Anisa M; Bunga Adventine Samosir; Ivan Darmawan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Government has an important role to play in meeting the diverse needs of communities through public services. One of the public services supported by the government is the e-KTP (electronic identity card) service. However, the implementation of e-KTP services in Ujungberung District, Bandung City has not been optimized yet. This study aims to test the responsiveness of e-KTP services in Ujungberung district. In this study, the literature review method with the response theory of Ansoff and McDonnel is used. The research results indicate that there are several problems in the implementation of e-KTP services in Ujungberung district, including lack of adequate infrastructure, lack of service responsiveness from agents and service providers. does not meet e-KTP production operation standards, as well as public complaints and grievances about the quality of e-KTP service in Ujungberung District. Responsiveness of public services is the key to community satisfaction. Responsiveness or responsiveness of public services is the key to community satisfaction. The government should strengthen the responsiveness of e-KTP services in Ujungberung District by improving facilities and infrastructure, improving the quality of service agents and improving operational standards. motion.